Successful Management of Dystocia due To Narrow Pelvis in a Queen - SINGH, A K; GANDOTRA, V K; SINGLA, V K (The Indian Journal of Animal Reproduction, 2023)
A rare case of dystocia in queen due to narrow pelvis and its successful management is reported.
Keywords: Dystocia; Narrow pelvis; Queen